Factors Affecting Brand Awareness in Central Region of Malaysia: a Study on FPTT - Xin Ling, Kerk; Fazli Mohd Sam, Mohd; Feisal Ismail, Albert (International Journal of Engineering and Technology, 2018)
Brand awareness is the ability of potential consumers to recognize or recall of the certain brand from a certain product category. Brand Awareness has been infiltrated in service sectors across the world as well as education sector. In fact, creating brand awareness in universities is much more difficult than a product as the complexity of marketplace has increased tremendously. This research is to study the factors affecting brand awareness of higher education institution. The study obtained data from 243 respondents including students, parents and workers from central region of Malaysia. In this study, the research design used by the researcher was descriptive research design. The results indicate that service quality, advertising and promotion, reputation and employability have significant relationship with brand awareness of Faculty of Technology Management and Technopreneurship (FPTT).